Electrostatically driven drumhead resonators based on freestanding membranes of cross-linked gold nanoparticles. Issue 35 (29th July 2016) - Schlicke, Hendrik; Schröter, Clemens J.; Vossmeyer, Tobias
Abstract : We present the first electrostatically driven drumhead resonators employing freestanding membranes of dithiol cross-linked gold nanoparticles with fundamental resonance frequencies in the high kHz range and quality factors of up to ∼2000. Abstract : Freestanding, nanometer-thin membranes of alkanedithiol cross-linked gold nanoparticles represent elastic, mechanically robust and electrically conductive materials, which are interesting for the fabrication of novel nano- and microelectromechanical devices. In this work we present the first electrostatically driven drumhead resonators based on such nanoparticle membranes. These circular membranes have a thickness of 33 to 52 nm, a diameter of either 50 μm or 100 μm, and are equally spaced from their back electrode by ∼10 μm. Using an interferometric nanovibration analyzer various vibrational modes with resonance amplitudes of up to several 100 nm could be detected when the membranes are excited by applying AC voltages (<30 V) with drive frequencies of up to 2 MHz. Further, spatial amplitude distributions of different vibrational modes could be imaged. The devices showed fundamental resonance frequencies in the high kHz range and quality factors Q up to ∼2000. Finally, vibrational spectra and observed mode patterns could be well interpreted using the theory for a clamped circular membrane with negligible bending stiffness. Our findings mark an important step towards the integration of freestanding gold nanoparticle composite membranes into electromechanical devices with various applications, such as novel types of pressure or mass sensors.